Synthesis and biological studies of benzofuran-based estrogen receptor α modulators, pyridone alkaloids and zanamivir - Leow, Min Li (2014)
In the first chapter, the search for new estrogen receptor alpha (ERα) modulators commenced with a trial molecular screening and 5,6-dihydroxybenzofuran was identified as a possible drug target for ERα. The target molecular modelling compound and a series of 5,6-dihydroxybenzofurans were synthesized and evaluated for their anti-proliferation activities against MCF-7 and MDA-MB-231 breast cancer cells. From the Structure-Activity Relationship (SAR) studies, potential functional groups were identified. The two hydroxyl groups at C-5 and C-6 and the phenyl ring at C-2 positions were found to influence the bioactivity significantly, as considerable cytotoxicity was observed in MCF-7 breast cancer cells. In addition, the apoptotic abilities of the compounds were measured in both MCF-7 (ER+) and MDA-MB-231 (ER-) cells. The results demonstrated that our compounds inhibit MCF-7 breast cancer cells via ER+. These preliminary results provide valuable information towards the identification of important functional groups present on 5,6-dihydroxybenzofuran, which could potentially be a promising scaffold for designing novel ER ligands.